2016
DOI: 10.1007/s00420-016-1157-z
|View full text |Cite
|
Sign up to set email alerts
|

Higher risks when working unusual times? A cross-validation of the effects on safety, health, and work–life balance

Abstract: Work at unusual times constitutes a considerable risk to social participation and health and showed structurally consistent effects over time and across samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 29 publications
3
29
0
2
Order By: Relevance
“…Previous research has found an association between work-life conflict and evening shifts (Greubel et al, 2016) and rotating three shift work (Camerino et al, 2010;Fujimoto et al, 2008), but no association with frequency of night work (Dahlgren et al, 2016).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous research has found an association between work-life conflict and evening shifts (Greubel et al, 2016) and rotating three shift work (Camerino et al, 2010;Fujimoto et al, 2008), but no association with frequency of night work (Dahlgren et al, 2016).…”
Section: Discussionmentioning
confidence: 83%
“…In a nurse sample, non-night and rotating shift workers were at a significantly increased risk of poor family function compared to day workers (Tai et al, 2014). Consistent results show that a high number of weekends or Sundays at work increases work-family conflict (Camerino et al, 2010;Greubel et al, 2016;Wirtz et al, 2011;Wirtz and Nachreiner, 2010). Furthermore, long working hours have been shown to increase workfamily interference (Eurofound, 2016), especially in the absence of control over working times (Hughes and Parkes, 2007).…”
Section: Introductionmentioning
confidence: 93%
“…The PNWs and DWs also reported less often work-life conflict than SWs. To the best of our knowledge, there are no previous studies comparing the same working time regimes than this study, but there is previous research showing that work including evening work is disruptive for worklife balance (Greubel et al, 2016.…”
Section: Discussionmentioning
confidence: 91%
“…Shift work, especially rotating shifts, can disrupt workers' circadian rhythms, resulting in sleep disturbances and private life interference 38) . Previous studies have shown that increased proportion of evening shifts 28,33) , weekend work 29) , and quick returns 39) were associated with an increased risk of WLC. Therefore, nurses may be at greater risk of WLC than other healthcare workers.…”
Section: Fig 1 Worklife Balance and Worklife Conflict Among Employementioning
confidence: 95%